Crystal structure of 3-acetoxy-2-methylbenzoic acid - Saranya, Matheswaran (Acta Crystallogr E Crystallogr Commun, 2015)
In the title molecule, C(10)H(10)O(4), the carboxylic acid group is twisted by 11.37 (15)° from the plane of the benzene ring and the acetoxy group is twisted from this plane by 86.60 (17)°. In the crystal, molecules are linked by pairs of O—H⋯O hydrogen bonds, forming inversion dimers with the expected R (2) (2)(8) graph-set motif.